Changing the domain of a boundary value problem - Dinh, Ta Van (Journal of Computer Science and Cybernetics, 2015)
We try to replace a given boundary value problem on a multidimensional domain with nonsmooth boundary by another one on an approximative domain with smooth enough boundary. The convergence of the solution of the approximative problem to that of the given problem is proved.